Impact of an urban regional medical campus: perceptions of community stakeholders - Gerry Cooper (Canadian Medical Education Journal, 2020)
Background: Regional medical campuses (RMC) have shown promise in addressing physician shortages. RMCs have been positively evaluated in rural/remote communities, however, it is unclear whether this model will be as beneficial in underserved urban areas. This study evaluated the impact of a RMC on a midsized urban city (Windsor, Ontario). We compare our results with a similar study conducted in a remote community in British Columbia (BC).